THE ROLE OF ERYTHROPOIETIN IN TREATMENT OF ANEMIA IN CANCER PATIENTS - P. G. Berezin; V. V. Milovanov; A. A. Ivannikov (Исследования и практика в медицине)
Malignant neoplasms are a serious pathological condition, both in terms of the course of the disease and the need for treatment, and a prognosis for the life of patients. The deterioration in the quality of life, social disadaptation (reduced physical activity, job change, fatigue, etc.) is a complication of the course of the disease caused by the development of anemia, which requires a vital need for its correction. This article analyzes the efficacy of recombinant erythropoietin — Epoetin-theta in the treatment of patients with NON — myeloid tumors and CRF (chronic renal failure) in cancer patients. The high efficacy and safety of drug therapy in this category of patients are demonstrated. Recommendations are given on the optimal dose of the drug in order to obtain the most pronounced clinical effect of treatment, increasing the therapeutic dose of the drug with an insufficient increase in the hemoglobin level by 100% or more allows an individual approach to the correction of anemia. The possibility of its application in routine clinical practice of the oncologist’s doctor, namely in out-patientpolyclinic conditions, has been determined.